Primary tooth enamel loss after manual and mechanical microabrasion - Zuanon, Ângela Cristina Cilense [UNESP]; Santos-Pinto, Lourdes [UNESP]; Azevedo, Elcilaine Rizzato [UNESP]; Lima, Luciana Monti [UNESP] (My University, 2008)
Purpose: This study's purpose was to assess the amount of dental enamel loss on primary incisors after manual or mechanical microabrasion with a phosphoric acid/pumice paste. Methods: Ten exfoliated primary maxillary incisors were bisected faciolingually and the resulting 20 halves were randomly assigned to 2 groups: group 1 (n=I0)-manual technigue (plastic spatula); and group 2 (n=I0)-mechanical technigue (rubber cup attached to a low-speed handpiece). Microabrasion was performed on the buccal surface using an abrasive paste prepared with 37% phosphoric acid and pumice. Ten 20-second applications alternated with 20-second risings were performed in each group. Enamel thickness measurements made under stereomi-croscopy before and after microabrasion were analyzed statistically by analysis of variance and pairwise ttest Results: There was a statistically significant difference (P=.003) between the manual and mechanical technigues. The mechanical technigue produced a mean enamel loss of 274.16 μm (66% of total enamel thickness), while the mean enamel loss with the manual technigue was 152.59 μm (39% of total enamel thickness). Conclusion: Manual microabrasion using a plastic spatula removed less enamel, but was sufficient to eliminate most superficial stains and defects, and may be a viable option for the microabrasive technigue on primary teeth.
Keywords: Dental enamel; Microabrasion; Primary teeth